COMMUNICATIVE GENRES IN SOCIAL MEDIA: A COMPARATIVE PRAGMATIC PERSPECTIVE - Sherzod Rabbimkulovich Yuldashev (Bright Mind Publishing, 2026)
This article examines the pragmatic significance of communication genre features in English and Uzbek social networks through a comparative analysis. The study applies corpus-informed discourse analysis and speech act theory. Findings show that genre markers regulate credibility, intimacy, stance, and evaluative alignment. The paper proposes operational criteria for describing social-media genres across languages and platforms.
Keywords: Social networks, communication genre, pragmatics, speech acts, discourse, indexicality, audience design.